Tunicamycin Anticancer Drug May Reliable to Treat Coronavirus Disease-19 - Dawood, Ali; Alnori, Haitham Abdul-Malik (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: SARS-CoV-2 outbreaks remains a medical and economic challenge, due to the lack of a suitable drug or vaccine. The glycan in some proteins plays an important role in protein folding, sorting, transport, and oligomerization, so the hindering of N-linked glycosylation of glycoproteins will prevent assembly of the virion. Tunicamycin anticancer drug inhibits the N- linked glycan. AIM: This study aimed to find out the mechanism action of tunicamycin on the viral glycoproteins. RESULTS: The growth of the virus in the presence of tunicamycin conducted in the production of non-infectious and absence of spike protein (spikeless virions). Tunicamycin inhibits E2, S, and M glycoproteins of coronaviruses. Tunicamycin has also diminished glycosylation of PTMs such as HE, and 8ab of SARS-CoV. Finally, CONCLUSION: This study recommends using this drug to treat the SARS-CoV-2.